IMPLEMENTASI PROGRAM PEMUTIHAN PAJAK KENDARAAN BERMOTOR DI SAMSAT SUMBER KABUPATEN CIREBON PROVINSI JAWA BARAT - Subhan, Subhan; Azis, Sukron Ibnu; Fadhlillah, Farhan De (Universitas Tulungagung, 2026)
This study aims to analyze the implementation of the motor vehicle tax amnesty program at the Sumber Tax Office (SAMSAT), Cirebon Regency, West Java Province. In the context of regional autonomy, motor vehicle tax (PKB) serves as a crucial source of revenue to support infrastructure development and public services. The tax amnesty program, known as the tax amnesty, is designed to increase taxpayer compliance by eliminating fines for delinquent vehicle owners. The research method used is descriptive qualitative, allowing researchers to deeply understand the dynamics and factors influencing the implementation of this policy. The results indicate that the tax amnesty program has successfully increased the number of taxpayers paying their arrears and provided an opportunity for the public to fulfill their tax obligations without the burden of fines. However, challenges such as a lack of equitable information and economic variations that affect payment ability remain obstacles. This study also identifies the importance of public outreach and education to raise awareness of tax obligations. Recommendations include the need to increase training for SAMSAT officers to improve service and communication quality, and to strengthen outreach strategies to ensure information about the amnesty program is accessible to all levels of society. Thus, the tax amnesty program is expected to contribute positively to tax compliance and local revenue in Cirebon Regency. Keywords: Implementation of the program, Vehicle tax amnesty, West Java